Layanan Bimbingan Kelompok Dengan Teknik Behavior Contract Untuk Mengurangi Kebiasaan Bermain Game Online - Setyo Budi Utomo (Universitas Muria Kudus, 2021)
This study aims to determine whether group guidance services with behavior contract techniques can reduce the habit of playing online games in class VIII students of SMP Negeri 1 Bancak in the odd semester of the 2019/2020 academic year. This study was designed with a counseling guidance action research approach. The data analysis technique in this research is comparative descriptive, which is to compare the service results and the improvement of the group guidance service process in each cycle. The subjects of this study were class VIII students of SMP Negeri 1 Bancak with the number of participants in group guidance, namely 10 students, all of whom were male. From the results of the implementation of this 2-cycle research, it can reduce the habit of playing online games as evidenced by the decrease in the average in the pre-cycle stage to the first cycle of 5.7 (9.91%) which then decreases again from the first cycle to the second cycle with an average 12.6 (24.32%). In the initial conditions, the habit of playing online games was in the high to medium category after being given group guidance services with behavior contract techniques in cycle II. In addition, further evidence was the increase in the quality of the group guidance service process from cycle I to II, as evidenced by an increase in the average score of 19.67 with a percentage of 33.72%.